Predominant regeneration strategy results in species-specific genetic patterns in sympatric Nothofagus s.s. congeners (Nothofagaceae) - Acosta, María Cristina; Mathiasen, Paula; Premoli Il'grande, Andrea Cecilia (Australian Journal of Botany)
Life-history traits affect plant performance. Predominant regeneration modes, sprouting v. non-sprouting, will result in contrasting evolutionary and ecological responses that may be traced by nuclear markers. Sympatric Nothofagus Blume species provide the natural setting to test whether sprouters have a greater ability to maintain genetic diversity. In total, 28 populations along the entire distribution range of N. antarctica (G. Forst.) Oerst. were screened by eight polymorphic isozyme loci. We compared pairwise genetic patterns of the predominant sprouter N. antarctica with the mainly non-sprouter N. pumilio (Poepp. & Endl.) Krasser at 20 sympatric locations along their geographically concordant widespread range. Overall, the sprouter N. antarctica showed higher genetic variation throughout its range than did the non-sprouter N. pumilio. Mid-latitude populations of N. antarctica have maintained isozyme diversity, as inferred using genetic-landscape analysis. Despite the potential for inter-specific gene flow and past hybridisations, species identity was preserved by divergent selective forces acting on sympatric populations with distinct autoecological traits. Predominantly sprouting, as compared with mainly non-sprouting, has favoured long-term persistence of genet diversity in relatively large populations that were probably less affected by drift through time, thereby preserving molecular variants along its range. These variants, in combination with plasticity in diverse habitats, have resulted in greater resilience of N. antarctica under changing scenarios. Fil: Acosta, María Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Mathiasen, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...